1991
DOI: 10.3382/ps.0702074
|View full text |Cite
|
Sign up to set email alerts
|

Altered Metabolism of Carotenoids During Pale-Bird Syndrome in Chickens Infected with Eimeria acervulina

Abstract: The progression of changes in carotenoid metabolism during pale-bird syndrome caused by a coccidial infection was investigated. Male broiler chickens 15 days of age on a yellow corn and soybean meal-based diet were infected with Eimeria acervulina oocysts and their serum, liver, and toe webs were sampled at 0, 4, 6, and 10 days postinfection for HPLC analysis of carotenoids. At 4 days postinfection a drastic reduction (71%) in serum lutein, the main body carotenoid, and smaller reductions in liver (58%) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Several investigators have found relationships that suggest carotenoids in birds may be compromised by challenges to an individual's health. Such results include associations between coloration, or carotenoid levels, and condition Bortolotti et al 1996), exposure to parasites (Bletner et al 1966;Tyczkowski & Hamilton 1991) and environmental contamination (Eeva et al 1998;Camplani et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have found relationships that suggest carotenoids in birds may be compromised by challenges to an individual's health. Such results include associations between coloration, or carotenoid levels, and condition Bortolotti et al 1996), exposure to parasites (Bletner et al 1966;Tyczkowski & Hamilton 1991) and environmental contamination (Eeva et al 1998;Camplani et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…21,63,64 The use of stable isotopes enables a much more accurate assessment of β-carotene bioavailability and utilisation to be made. However, such studies have been done with subjects who have normal or marginal vitamin A status, may have subclinical inflammation but are never vitamin A deficient.…”
Section: Stable Isotope Studies Use Of Stable Isotopes To Determine Bmentioning
confidence: 99%
“…Work in chickens has also shown that acute infection is associated with a 71% reduction in serum lutein concentrations, 4 days post infection with coccidiosis. 21 Lutein is the main carotenoid found in the blood and other tissues in the chicken. Furthermore, lutein concentrations continued to be lost from the tissues 10 days post infection.…”
Section: Carotenoids and Inflammationmentioning
confidence: 99%
“…From the diseases that influence skin pigmentation, coccidiosis is perhaps one of the most frequent and costly infections that affect the poultry industry globally Fuller 1975, Tyczkowski andHamilton 1991). The severity of the coccidiosis effect on skin pigmentation will depend on the Eimeria strain and virulence, immune status of the bird, and other complicating factors.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the coccidiosis effect on skin pigmentation will depend on the Eimeria strain and virulence, immune status of the bird, and other complicating factors. E. acervulina and E. maxima produce a significant reduction in plasma carotenoids (Ruff and Fuller 1975, Sharma and Fernando 1975, Ogbuokiri and Edgar 1986, Tyczkowski and Hamilton 1991. These infections are sometimes associated with lower body weight gain (BWG) that is a consequence of poor nutrient absorption due intestinal sloughing and villi shortening (Allen 1987).…”
Section: Introductionmentioning
confidence: 99%